Community engagement as a liminal space of translanguaging - Thondhlana, Mazvita; McKenna, Sioux (Critical Studies in Teaching and Learning, 2024)
Community engagement is, in many ways, a liminal space, in that, while it is a space of teaching and learning and sometimes of engaged research, it is neither fully academic nor ‘non-academic’. Liminal spaces can allow for upending of the hierarchies that are characteristic of more closely controlled educational settings. The participants in this study, all of whom participated in a community engagement project, known as the Engaged Citizen Programme, spoke extensively about the translanguaging affordances of liminal community engagement spaces. The data suggests that translanguaging, primarily of isiXhosa, Afrikaans, and English, was central to the community engagement activities. The participants indicated that the usual lines of linguistic privilege experienced in the university were upended in the community setting. The extent to which multilingualism is fostered in the community engagement space is an example of how lessons learned in community engagement could benefit teaching and learning in the classroom.